Design and experiment of the ditching device with combined rotary tillage and chisel shovel for lateral deep fertilization in tea garden - Liang, Fang; Wang, Yubing; Yu, Yizhe; Zheng, Haonan; Huang, Youyi (International Journal of Agricultural and Biological Engineering, 2025)
To solve the difficulty in ditching for the deep fertilization in tea gardens caused by the high quantity of tea branches and stubbles, a new ditching device combined with a kind of rotary tillage and chisel shovel was designed. The combined ditching device worked by the following steps: Firstly, the stubble, such as fallen leaves and weeds between the rows, was cleaned up and thrown away by the rotary tillage. Then, the chisel-shaped fertilizing shovel forcefully dug into the soil, realizing the deep fertilization groove. The parameters of the rotary tillage and stubble-throwing device and the chisel-shaped fertilizing shovel were optimized by single factor test and quadratic regression orthogonal rotation test, respectively. The optimization results showed that when the number of stubble-throwing blades of the rotary tillage and stubble-throwing device was five, and the blade installation inclination angle was 16°, the stubble removal rate was the highest at the high speed of the cutter (300 r/min), which was 91.64%. When the entry angle of the chisel-shaped fertilizing shovel was 30°, the entry clearance angle was 8°, and the operating speed was 0.7 m/s, the stability coefficient of the groove depth was 94.9%, which was the optimal parameter of the chisel-shaped fertilizing shovel. The field experiment showed that the average width of the ditching was 224 mm (between 202-248 mm), the average depth of the groove was 194.9 mm (between 173-218 mm), and the stability coefficient of the groove depth could reach 92.78%, realizing stable lateral deep fertilization in the tea garden.Keywords: tea garden, rotary tillage and stubble throwing, chisel shovel fertilizer, combined ditching, parameters optimizationDOI: 10.25165/j.ijabe.20251803.9065Citation: Liang F, Wang Y B, Yu Y Z, Zheng H N, Huang Y Y. Design and experiment of the ditching device with combined rotary tillage and chisel shovel for lateral deep fertilization in tea garden. Int J Agric & Biol Eng, 2025; 18(3): 116–123.